Letramento acadêmico : o processo ensino e aprendizagem da resenha no ensino superior - Souza, Emili Coimbra de (2017)
The study proposal of this dissertation is the text production of the critical review genre in higher education, which is one of the most common genres in this educational environment and it is requested from students during their academic journey. Hence, a Didactic Sequence (DS) was applied. The corpus of analysis included 18 reviews produced by the students from a second term class of the Management course of a university center in southern state of Paraná, Brazil. The general objective was to identify the main problems presented in the production created by the students about the critical review genre, and later to create and apply a Didactic Sequence aiming to contribute to student learning regarding this academic genre. This work presents the following specific objectives: to verify the previous knowledg of students regarding text production of the review text genre, associated with characteristics of academic literacy; to analyze the initial text productions of the review genre regarding structure, style, and theme content; to reallocate the previous knowledge of students to the demands of written practice of the review genre upon the application of DS; and to verify whether students acquired or enhanced their knowledge regarding the production of critical reviews, from initial text productions (IP) and final text productions (FP) of the review genre after DS application. The main theorists used for theoretical approach on literacy were Carlino (2002, 2003, 2009), Kleiman (2008), Marcuschi (2007), Soares (2002, 2004, 2011,2014). The considerations on discursive and theoretical genres were essential in the reflections by Bakhtin (2003), Marcuschi (2003, 2008), Rojo (2005), and Schneuwly and Dolz (2013). The DS approach was based on the studies by Dolz, Noverraz, and Schneuwly(2013), who suggest steps to develop a DS. Additionally, existent studies were presented on the critical review genre by Brazilian researchers over the last years, from the analysis of dissertations and theses. In the DS application, which is the proposal of this research for applying studies on the critical review genre, the works were based on studies by Dolz, Noverraz, and Schneuwly (2013). In this sequence, activities that included the challenges identified in initial productions and that aided the definition of categories of text production analyses were developed. The use of the DS allowed the researcher a better follow-up and analysis of actions triggered during the application of modules along with the participants of the research and the study object, characterizing this research as an explanatory, participative action research. The results obtained in this scientific investigation allowed observing that the use of DS in the teaching and learning process contributes to the acquisition/enhancement of knowledge on text genres in higher education and shows the need for resuming studies on 8 specific subjects such as summary creation, critical appreciation of source texts, and the use of direct citations in critical review productions, considering that learning is in constant development.